Peran Pendidikan Digital dalam Melindungi Privasi Pengguna dan Mencegah Dampak Sosial - Amelia Salsabisa Hakim; Hakim, Amelia Salsabisa; Mustaqim, Putri Jihan; Atha Naufal (LPPM Universitas Sains dan Teknologi Komputer, 2025)
In the digital era, personal data protection has become a crucial issue due to the growing risks of privacy breaches. This study aims to explore the role of digital education in enhancing privacy literacy and mitigating the social impacts of data violations. Utilizing a mixed-methods approach, primary data was collected through online surveys and in-depth interviews with users and experts, while secondary data was analyzed from academic journals and industry reports. Results reveal that only 42.7% of respondents understood how to safely manage their personal information, reflecting a significant gap in privacy awareness. Moreover, a positive correlation (R = 0.72) was identified between improved privacy literacy and reduced social risks, such as identity theft and cyberbullying. Simulations proved to be effective educational tools, with every 10% increase in digital privacy literacy reducing social risks by 7%. The findings highlight the need for integrating privacy education into formal curricula at all educational levels, complemented by community-based initiatives for underserved populations. Collaborative efforts between governments, educational institutions, and technology organizations are essential to develop relevant and effective learning resources. The study underscores the importance of adopting holistic educational strategies to empower individuals in navigating the challenges of data protection in the digital age.